النشاط البدني المكيف ودوره في تعزيز الوعي الصحي لدى الأطفال ذوي الإعاقة العقلية البسيطة - فئة من 05 إلى 07 سنوات – دراسة ميدانية بالمركز النفسي البيداغوجي للمعوقين ذهنيا بالبرواقية ولاية المدية - مناصري محمد; Supervisor أ.د تمار محمد (Mohamed Boudiaf University of M'sila, 2024)
الملخص: بالعربية (عبارة عن فقرة): تضمنت هذه الدراسة إبراز مدى فاعلية ودور النشاط البدني الرياضي المكيف في تعزيز الوعي الصحي لدى الأطفال ذوي الإعاقة العقلية البسيطة فئة من خمسة إلى سبع سنوات ،وتمثلت الفرضية العامة في أن للنشاط البدني الرياضي المكيف دور في تعزيز الوعي الصحي لدى الأطفال ذوي الإعاقة العقلية البسيطة من وجهة نظر المربين ،وقد استخدم الباحث المنهج الوصفي التحليلي في دراسته، وشملت عينة الدراسة الأطفال ذوي الإعاقة العقلية البسيطة من وجهة نظر المربين المشرفين عليهم بالمركز وبذلك اعتمد على العينة المقصودة، وعلى ضوء ما أسفرت عليه نتائج الدراسة الحالية تبين فعلا أن للنشاط البدني الرياضي المكيف دور في تعزيز الوعي بالصحة الشخصية، بالتغذية السليمة، بالممارسة الرياضية، بالوقاية من الأمراض والمخاطر، بالقوام و بالتالي له دور في تعزيز الوعي الصحي لدى الأطفال ذوي الإعاقة العقلية البسيطة من وجهة نظر المربين المشرفين عليهم بالمركز. عنوان الدراسة: النشاط البدني المكيف ودوره في تعزيز الوعي الصحي لدى الأطفال ذوي الإعاقة العقلية البسيطة( فئة من 05 إلى 07 سنوات) أهداف الدراسة: • تحديد فاعلية الأنشطة البدنية المكيفة ودورها في تعزيز الوعي الصحي لدى الأطفال ذوي الإعاقة العقلية البسيطة • تحديد المهارات والمفاهيم والسلوكيات الصحية الصحيحة التي يجب تعزيزها للأطفال ذوي الإعاقة العقلية البسيطة مشكلة الدراسة: هل للنشاط البدني المكيف دور في تعزيز الوعي الصحي لدى الأطفال ذوي الإعاقة العقلية البسيطة فرضيات الدراسة: للنشاط البدني الرياضي المكيف دور في تعزيز الوعي الصحي لدى الأطفال ذوي الإعاقة العقلية البسيطة 1. للنشاط البدني المكيف دور في تعزيز الوعي بالصحة الشخصية لدى الأطفال ذوي الإعاقة العقلية البسيطة 2. للنشاط البدني المكيف دور في تعزيز الوعي بالتغذية السليمة لدى الأطفال ذوي الإعاقة العقلية البسيطة 3. للنشاط البدني المكيف دور في تعزيز الوعي بالممارسة الرياضية لدى الأطفال ذوي الإعاقة العقلية البسيطة 4. للنشاط البدني المكيف دور في تعزيز الوعي بالوقاية من الأمراض والمخاطر لدى الأطفال ذوي الإعاقة العقلية البسيطة 5. للنشاط البدني المكيف دور في تعزيز الوعي بالقوام لدى الأطفال ذوي الإعاقة العقلية البسيطة المنهج المتبع في الدراسة: المنهج الوصفي الأدوات المستخدمة في الدراسة: الاستبيان الكلمات المفتاحية : النشاط البدني الرياض للمكيف، الوعي الصحي، طفل الروضة ذو الإعاقة العقلية البسيطة بالفرنسية: Mots clés : Activité physique sportive adaptée, Sensibilisation à la santé, Enfant de maternelle Avec un léger handicap mental. بالإنجليزية: Keywords : Adapted physical sports activity, health awareness, Kindergarten Child with mild Montel disability جاء هذا البحث في فصول الفصل الأول: الإطار العام للدراسة وتناول الفصل الثاني: النشاط البدني الرياضي المكيف أما الفصل الثالث: الوعي الصحي الفصل الرابع: طفل الروضة ذو الإعاقة العقلية البسيطة من أهم النتائج التي توصل إليها الباحث : • للنشاط البدني الرياضي المكيف دور في تعزيز الوعي بالصحة الشخصية، بالتغذية السليمة، بالممارسة الرياضية، بالوقاية من الأمراض والمخاطر، وأخيرا بالقوام لدى الأطفال ذوي الإعاقة العقلية البسيطة • للنشاط البدني الرياضي المكيف دور في تعزيز الوعي الصحي لدى الأطفال ذوي الإعاقة العقلية البسيطة توصل الباحث للعديد من التوصيات أهمها : • تصميم برامج للتربية الصحية للأطفال ذوي الإعاقة العقلية في ضوء معايير التربية الصحية العالمية • دراسة الفروق بين تأثيرات الأنشطة الرياضية المكيفة على الأطفال بمختلف أنواع ومستويات الإعاقة العقلية كشاف بالإنجليزية Institute of science and technology of physical activities and sports Département : physical education Serial number : Registration number: 23042049284 Recearcher : Menasri Mohamed Discussion History: 05-06-2024 Mimo title : Adapted physical sports activity and its role in promoting Health awareness among children with mild mental disabilities, ages five to seven years. A yield study at the psychological and Pedagogical center for the mentally disabled in berrouaghia, Media state Language of memo : Arabe Memo type: Master Country : People’s democratic republic of algeria-M’sila state- The university : University of M’sila Supervision of Prof : Tamar Mohamed Grade : Doctor Nombre de page : 130 pages (Cd-Rom* word * PDF) Electronic file Spécialisation : Adapted physical sports Activity and health Branch : Adapted physical sports activity Summary in English ( A paragraph ) : This study included highlighting The effectiveness and role of adopted sports physical activity in promoting health among children with mild mental disabilities,aged five to seven years,The general hypothesis was that adapted Sports physical activity Has a role in promoting His awareness among Children with mild mental disabilities from the point of view of the educators, the researcher used the descriptive analytical method in his study, the study sample included children with mild mental disabilities From the point of view of the educators supervising them at the center.thus,He relied On the intended Sample, and in light of what the result of the Current Study result in,it actually became clear that the activity Physical has a role in enhancing Personal health awareness , Proper nutrition and exercise ,and desease Prevention and risk,maintaining strength and therefore Has a role in Enhancing health awareness among People children with With mild mental disabilities from the point of educators supervising them at the center. Objectives the study : • Determine the effectiveness of adapted physical activities and their role in promoting health awareness among children with disabilities sample mentality. • Identifying The correct health skills, Concepted, and behavior that should be reinforced for children with Milk mental disabilities. problem of studying : Does adapted physical activity play a role in promoting health awareness among children with mild mental disability ? Study hypothses : - Adapted physical activity Has a role in promoting Health awareness Among children with mild mental Disability 1- Adapted physical activity has a role in enhancing awareness of personal health Among children with mild mental disability 2- Adapted physical activity has a role in enhancing awareness of proper nutrition Among children with mild mental disability 3- Adapted physical activity has a role in enhancing awareness oilities orts practic among children with mild mental disability 4- Adapted physical activity has a role in enhancing awareness of disease and the risk Prevention among children with mild mental disability 5- Adapted physical activity has a role in enhancing awareness of texture among children with mild mental disability The method Followed in the study : Descriptive method Tools used in the study : Questionnaire keywords : Adapted physical activity, Health awareness, Kindergarten child with mild mental disability This research was presented In chapters Chapter 01 :The general framework Of the study chapter 02 : adapted physical activity chapter 03 : Health awareness chapter 04 : kindergarten child with mild mental disability The most important Result reached By the research: 1. Adapted physical activity Has a role in enhancing awareness Of personal health Through proper nutrition, Exercise, and Prevention of diseases And physical risk In children with mild mental disability 2. Adapted physical activity has a role in Promoting health awareness Among children with mild mental disability The researched reached many Recommendation the most important of f which is : • Designing health Education programs For children with Mental disabilities In light of International health Education standards • Studying the difference Between the effect of adapted sports Activities on children with Different types and levels of montel disability.
Keywords: الوعي الصحي; طفل الروضة ذو الإعاقة العقلية البسيطة; النشاط البدني الرياض للمكيف